Videographic performativity and the occupation of online space: OUTROS Art Festival - Sarzi-Ribeiro, Regilene Aparecida [UNESP]; Rocha, Cleomar de Sousa; Martinez, E.; DosSantos, FCS; Perez, E. M. (Univ Politecnica Valencia, 2022)
The theme of this research is videographic performativity and it arose from the observation of the competence of video language to interact with different subjects and virtual environments, acting as a transmitting agent of characteristics of audiovisual language, which result in the incorporation of video as a cultural practice. The electronic aesthetics associated with experimental poetics causes mutations in the basic structures of video, giving rise to other audiovisual forms, the result of videographic performativity. For this work, we present the description and critical reading of a set of video works that participate in the online event OUTROS Art Festival (2021), an exhibition with the aim of taking over the space of the network, online, having the virtual as the locus of video compositions shown live. In the proposed methodology, video is considered a cultural practice in which videographic performativity -technical and poeticis the key to understanding video as a cultural phenomenon, from which we have inhabited the world. Inhabit, live, occupy, are verbs that translate into actions and forms of presence, of being and being in the world, giving it the configuration, a design that is the result of audiovisual language and its viral behavior that contaminates and turns into action. And it is clearer than ever that we have inhabited the world videographically, occupying spaces, places, territories audiovisually. The results show that one aspect of the emerging videographic performativity of the times of the COVID-19 pandemic is the expansion of collective videographic practices and the exponential growth of audiovisual manifestations generated by the feeling that telepresence does not replace reality. rather, it conditions and shapes our cultural behavior to the extent that we occupy virtual space poetically and do so videographically.
Keywords: Video art; videographic performativity; OUTROS Art Festival; COVID-19 pandemic